EFFECTIVENESS OF ONLINE LEARNING USING THE BLENDED LEARNING METHOD IN CLASS V STUDENTS SDN 7 BITTUANG, TANA TORAJA - Fri Elka; Sundari Hamid (Publikasi dan UKI Press UKI Toraja., 2023)
This research was conducted with the aim of knowing the effectiveness of online learning using the blended learning method for fifth grade students. This type of research is experimental research with a pre-experimental research design one-group pretest-posttest design, namely giving a test before treatment, then giving a test after treatment using the blended learning method. The sample of this research was 36 students of class V. This research was conducted in 6 meetings. Data collection techniques used in this study were performance text techniques, observation and documentation which were analyzed with descriptive statistics and inferential statistics. The data obtained were also analyzed using the t-test formula. The results of this study indicate that by using the blended learning method students are more active and dominate the learning process so that students do not easily feel bored or bored. It can be seen that based on the results of the t-test, the price = 3.252 and = 1.689 with the average student score before the treatment in working on the pretest questions is 60 and the average student score after being given treatment in working on the posttest questions is 88.61. Therefore it can be concluded that there is effectiveness of the blended learning method for increasing student learning outcomes in class V SD.